Strong correlation in surface chemistry. Issue 5 (13th April 2017) - Janesko, Benjamin G.
Abstract : Density functional theory (DFT) simulations of surface chemistry have emerged as a valuable complement to experiment. However, standard DFT methods do not always accurately model the 'strong' electron correlation effects seen in stretched covalent bonds. Such systems' ground-state wavefunctions are not well-described by single molecular orbital configurations. I review some of the challenges of strong correlation, and some methods used to simulate it in surface chemistry. I also use the electron delocalisation range function EDR( ), which quantifies the extent to which electrons at point delocalise over distance d, to highlight how a nearby metal cluster affects strong correlation in a dissociating covalent bond.